(untitled) (Global Journal of Management and Business Research, 2016)
This study examined the effect of leadership style (transformational and transactional) on turnover intention of employees in Westec Security Systems Ghana Limited. The study was quantitative, cross-sectional, descriptive and analytical in nature. Structured questionnaires was used for the data collection. Two hundred and fifty eight (258) questionnaires were returned by respondents out of 265 administered. The findings indicated a significant negative relationship between affective commitment and turnover intention (β= -.226, p